Perkembangan Individu Dan Kebutuhan Belajar: Perspektif Psikologi Dan Bimbingan Konseling Di SDN Sangkali - Adrian Nurul Arifin; Feida Noorlaila Isti’adah; Asti Rahmawati; Alin Nurliana; Desti Rahmasari; Hilda Nurhidayah; Neng Hilma; Zidan Fudhola (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to investigate the counseling and psychological guidance approaches applied by homeroom teachers at SDN Sangkali, Tasikmalaya City, in dealing with problems such as bullying and stress experienced by students. The methods used include observation and interviews to understand how teachers manage the emotions and pressure experienced by students. The research results show the importance of understanding students' individual development and learning needs to create a supportive learning environment in elementary schools. In particular, this research highlights the important role of homeroom teachers in dealing with problems such as bullying and stress resulting from bullying, as well as effective strategies in supporting students' psychological well-being.